Electroencephalography differences in children with and without bilateral cerebral palsy during unimanual and bimanual drumming tasks - Mathur, Arjun; Bulea, Thomas C.; Kline, Julia; Damiano, Diane L. (Frontiers in Human Neuroscience, 2026)
BackgroundMultiple studies have examined bimanual coordination in children with unilateral cerebral palsy (CP) with few in bilateral CP and none utilized electroencephalography (EEG). This study investigates brain activation underlying bimanual performance in individuals with bilateral CP and typical development (TD).MethodsTwenty-six participants (13 CP; 13 TD) completed the Box and Block Test (BBT) and visually cued drumming tasks with each hand (unimanual) and then with both hands synchronously and asynchronously (bimanual). EEG and motion data were recorded during drumming tasks.ResultsChildren with CP demonstrated bilateral impairments in drumming cadence and BBT, increased alpha and beta and decreased gamma EEG band activation in mainly non-dominant brain regions compared to TD. Bimanual tasks tended to show decreased performance and greater alpha and beta band activation than unimanual tasks for both groups. EEG activity and BBT correlations were positive in TD, but negative in CP.DiscussionThis study showed that children with CP had worse motor performance bilaterally and EEG activation differences from TD similar to previous unimanual findings in bilateral CP, however, a more complex bimanual task may have uncovered greater differences.ConclusionEvidence of bimanual deficits and EEG differences reinforces the need for greater research and clinical attention on upper limb function in bilateral CP.